Consumer Behavior In Virtual Goods Purchase Decisions On Online Gamers In Bengkulu City - Muhammad Ridho Ariansyah; Tito Irwanto; Tri Febrina Melinda (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to determine consumer behavior in virtual goods purchasing decisions for online gamers in Bengkulu City. The focus of this study is to determine whether the factors of impulsive buying, irrational buying and wastefulness in virtual goods purchasing decisions for online gamers in Bengkulu City. The method used is a quantitative method where data is obtained by distributing questionnaires to 100 online game users in Bengkulu City. The results of the analysis show that impulsive buying, irrational buying and wastefulness factors have a significant influence on online gamers' interest in virtual goods purchasing decisions in Bengkulu City, with the results of multiple linear regression tests Y = 1.599 + 0.430 X1 + 0.625 X2 + 0.053 X3. The t-test for the impulsive buying variable (X1) shows a significant value of 0.000 < 0.05, irrational buying (X2) of 0.000 < 0.05, and waste (X3) of 0.023 < 0.05, which means that Ha is accepted and Ho is rejected for the third variable. In addition, the f-test result of 0.000 < 0.05 shows that simultaneously the variables X1, X2, and X3 have a significant effect on Y.